Emergency Contraception: A Multi-specialty Survey of Clinician Knowledge and Practices. Issue 1 (January 2016) - Batur, Pelin; Cleland, Kelly; McNamara, Megan; Wu, Justine; Pickle, Sarah
Abstract : Obstet Gynecol Surv 2016;71(1):31–32 Although it is widely recommended that women at risk of unintended pregnancy receive counseling about emergency contraception (EC), a study published in 2011 found that only 3% of women had received such counseling in the past year. Ongoing contraception is highly effective at preventing pregnancy.